PRINSIP KONSISTENITAS PENGENDALIAN MASSA DALAM TRAGEDI STADION KANJURUHAN TAHUN 2022 - Chrysdianto, Dimas; Sidarta, Dudik Djaja; Hamdani, Fathul; Damayanti, Sri Sukmana (Gapenas Publisher, 2025)
The Kanjuruhan Stadium tragedy on 1 October 2022 was one of the darkest events in Indonesian sporting history, claiming hundreds of lives. This incident raises serious questions about the consistency of the police's application of crowd control principles as stipulated in Perkap No. 16 of 2006 and its compatibility with Article 359 of the Criminal Code. This study aims to answer two main questions: how did the police handle crowd control during the tragedy, and to what extent did their actions conflict with the national legal framework and human rights principles? This study uses a normative legal approach supported by sociological analysis. Primary data was obtained through interviews with police officers at the Malang Police Station and field observations, while secondary data was collected through a review of legislation, academic literature, and previous research. Data analysis was conducted qualitatively using inductive, deductive, and comparative methods to assess the gap between legal norms and field practices. The results of the study show that police actions were dominated by a repressive approach, particularly the use of tear gas, which triggered mass panic and caused a large number of casualties. These actions were not in line with the principles of proportionality, legality, and accountability as stipulated in Perkap No. 16 of 2006 and contradicted international standards on crowd control. Challenges in coordination among stakeholders, weak risk management, and the absence of emergency medical services further exacerbated the impact of the tragedy. This study concludes that the Kanjuruhan tragedy reflects institutional failure in the implementation of law and human rights protection. These findings imply the need for more humanistic crowd control policy reforms, based on human rights, as well as the integration of risk management in the organisation of public events. Further research is recommended to adopt a multidisciplinary approach encompassing legal, psychological, and crisis management aspects.